2020
DOI: 10.3389/fphar.2020.00460
|View full text |Cite
|
Sign up to set email alerts
|

Dandelion Polysaccharide Exerts Anti-Angiogenesis Effect on Hepatocellular Carcinoma by Regulating VEGF/HIF-1α Expression

Abstract: Recent studies have revealed that natural plants-derived polysaccharides exhibit potent anti-tumor activity. Our earlier studies suggest that dandelion polysaccharide (DP) inhibits hepatocellular carcinoma (HCC) cell proliferation in vitro and in vivo. Here, we investigated the effects of DP on the angiogenesis of HCC and the potential molecular mechanisms by which DP regulates angiogenesis. Wound-healing and transwell invasion assays revealed that DP inhibited HUVECs migration and invasion in vitro, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 31 publications
0
32
1
Order By: Relevance
“…Furthermore, it also reduces the protein expression of Bcl-2, an anti-apoptotic protein, in prostate cancer and human promyelocytic leukemia [ 11 , 14 , 15 ]. Moreover, the anti-angiogenic activity of several natural products has been reported in various cancer cells [ 16 , 17 , 18 ]. However, no evidence exists regarding the anti-tumor potential of fucoxanthin in canine mammary gland tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it also reduces the protein expression of Bcl-2, an anti-apoptotic protein, in prostate cancer and human promyelocytic leukemia [ 11 , 14 , 15 ]. Moreover, the anti-angiogenic activity of several natural products has been reported in various cancer cells [ 16 , 17 , 18 ]. However, no evidence exists regarding the anti-tumor potential of fucoxanthin in canine mammary gland tumors.…”
Section: Introductionmentioning
confidence: 99%
“…It regulates the expression of various chemokines involved in tumor growth, angiogenesis and metastasis [15] . Studies have shown that [16] hypoxia can promote HIF-1α mRNA and protein levels in Hepatoma cells. This experiment found that the expression of HIF-1α protein in the model group was signi cantly higher than that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (HUVECs) were purchased from Allcells (Shanghai, China) and cultured in the medium containing 50 U/mL penicillin and 50 U/mL streptomycin (Invitgen, San Diego, CA), 50 mL endothelial cell growth additive (Upstate, Temecula, CA), 2.2 g/L sodium bicarbonate, and 10% fetal bovine serum (Gibco, Grand Island, NY) under a humid environment at 37˚C with 5% CO 2 [19].…”
Section: Cell Culturementioning
confidence: 99%
“…Liu K et al showed that HIF-1α and VEGF expression in the serum of HCC patients was elevated after TACE [17]. Besides, inhibiting the HIF-1α/VEGF pathway under hypoxia chokes HCC tumorigenicity and angiogenesis [18,19]. Thus, inhibiting the HIF-1α/VEGF pathway has guiding signi cance for the treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%